Common Mental Disorders and Sickness Absence: A Register-Linkage Follow-Up Study Among Finnish Municipal Employees. Issue 6 (June 2018) - Mauramo, Elina; Lallukka, Tea; Lahelma, Eero; Pietiläinen, Olli; Rahkonen, Ossi
Abstract : Objective: This study examined how common mental disorders (CMD) at different severity levels are associated with short (1 to 3-day), intermediate (4 to 14-day), and long (15+ day) sickness absence (SA) among Finnish municipal employees. Methods: Survey data collected among the 40 to 60-year-old employees of the City of Helsinki in 2000 to 2002 were prospectively linked with employer's SA register data ( N  = 6554). Associations of CMD (GHQ-12) with SA in a 5-year follow-up were examined with quasi-Poisson regression. Results: Increasing GHQ-12 scores were associated with a higher number of SA spells. The highest GHQ-12 scores were associated with the highest number of short, intermediate, and long SA spells. Adjusting for social and health-related covariates attenuated the associations but they remained. Conclusion: Increasing severity of CMD increased the risk of short, intermediate, and long SA among Finnish employees. CMD should be tackled to prevent SA and promote work-ability among aging employees.